Діагностування як методологія оцінки стану гідротехнічних споруд - Качинський, А.Б.; Агаркова, Н.В. (Екологічна безпека та природокористування, 2012)
In work the analysis of methods of an estimation of a condition of hydroconstructions is carried out. The basic approach to this point in question research had been chose a method of diagnostics of difficult technical systems. Within the limits of this approach it was considered five mathematical methods of the research two of which are quantitative methods (the likelihood approach and automated diagnostic system Bajesa) and which allow to receive likelihood estimations of occurrence of failures on hydroconstructions of various classes of consequences, settlement values of probability of excess of the maximum expenses of water on the given objects and reliability factors on loading. Other considered three methods (the theory of indistinct sets, recognition of images and claster analysis) can be carried to a class of qualitative models which, in turn, can be applied to classification of conditions of objects of hydraulic engineering appointment and adjoining territories, and also monitoring of difficult systems which the system of hydraulic engineering constructions concerns also.